An ecological basic income? Examining the ecological credentials of basic income through a review of selected pilot interventions - Nicholas Langridge (University of Bath, Centre for Development Studies (CDS), 2021)
While basic income (BI) has long been advocated for its social benefits, some scholars also propose it in response to the ecological crises. However, the empirical evidence to support this position is lacking and the principles of an 'ecological basic income' (EBI), one with the potential to address the social and ecological crisis, are underdeveloped. This paper argues that an EBI should align with post-growth perspectives, aiming to lower material throughput, improve human needs satisfaction, reduce inequalities, rebalance productive activity towards the autonomous sphere, and shift societal values towards cooperation and sufficiency. It then examines how selected BI pilots have considered the principles of an EBI in their designs and evaluations and discusses what their findings infer about BI's ecological credentials. The results find ecological considerations to be largely absent from the implementation of BI pilots. However, their findings suggest that interventions adopting the principles of an EBI have the potential to address the ecological crises.
Keywords: 330; basic income; postgrowth; political ecology; sustainable development